2006 IEEE Symposium on Interactive Ray Tracing 2006
DOI: 10.1109/rt.2006.280217
|View full text |Cite
|
Sign up to set email alerts
|

On the Fast Construction of Spatial Hierarchies for Ray Tracing

Abstract: In this paper we will address the problem of fast construction of spatial hierarchies for ray tracing with applications in animated environments including non-rigid animations. We will discuss the properties of currently used techniques with O(N log N) construction time for kd-trees and bounding volume hierarchies. Further, we will propose a hybrid data structure blending a spatial kd-tree with bounding volume primitives. We will keep our novel hierarchical data structures algorithmically efficient and compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…Several techniques have been proposed to reduce the constants behind the asymptotic complexity. For example, Havran et al [16], Wald et al [33], and Ize et al [19] used approximate SAH cost function evaluation based on binning. Hunt et al [18] suggested using the structure of the scene graph to speed up the BVH construction process.…”
Section: Related Workmentioning
confidence: 99%
“…Several techniques have been proposed to reduce the constants behind the asymptotic complexity. For example, Havran et al [16], Wald et al [33], and Ize et al [19] used approximate SAH cost function evaluation based on binning. Hunt et al [18] suggested using the structure of the scene graph to speed up the BVH construction process.…”
Section: Related Workmentioning
confidence: 99%
“…They did not used low level optimization methods or kinds of methods are used to accelerate. Havran [13] recently proposed a method based on hierarchical acceleration structures in kd-tree. Moreover he introduced a SAH based on accelerate combined methods; using specification total 3D space will be formed.…”
Section: Previous Workmentioning
confidence: 99%
“…Therefore, a simple counter for each bin, like in conventional kD-tree binning methods, is not sufficient. Instead, we need to store one AABB per bin, similar to techniques for BVHs [Havran et al 2006;Wald 2007]. The actual binning process for a reference considers all bins that the reference AABB overlaps.…”
Section: Chopped Binningmentioning
confidence: 99%